Development of a new ferulic acid certified reference material for use in clinical chemistry and pharmaceutical analysis - Dezhi Yang; Fengfeng Wang; Li Zhang; Ningbo Gong; Yang Lv (Elsevier, 2015)
This study compares the results of three certified methods, namely differential scanning calorimetry (DSC), the mass balance (MB) method and coulometric titrimetry (CT), in the purity assessment of ferulic acid certified reference material (CRM). Purity and expanded uncertainty as determined by the three methods were respectively 99.81%, 0.16%; 99.79%, 0.16%; and 99.81%, 0.26% with, in all cases, a coverage factor (k) of 2 (P=95%). The purity results are consistent indicating that the combination of DSC, the MB method and CT provides a confident assessment of the purity of suitable CRMs like ferulic acid.